The impact of social media shared health content on protective behavior against COVID-19 - Mohammed, Fathey; Al-Kumaim, Nabil Hasan; Alzahrani, Ahmed Ibrahim; Fazea, Yousef (MDPI, 2023)
The use of social media has increased during the COVID-19 pandemic because people are isolated and working from home. The use of social media enhances information exchange in society and may influence public protective behavior against the COVID-19 pandemic. The purpose of this study is to identify the factors affecting public protective behavior when relying on COVID-19 pandemic-related content shared on social media. A model based on Protection Motivation Theory (PMT) was proposed and validated using a quantitative survey approach. A questionnaire was distributed to random respondents, and 488 responses were received and analyzed using SmartPLS software. The findings showed that perceived risk, e-health literacy, public awareness, and health experts’ participation influence public protective behavior when using social media to share COVID-19-relevant content. The outcomes of this study can enhance government agencies’ and public health care authorities’ understanding of how to use social media to raise awareness and reduce panic among the public.